Perancangan Alat Pengukur Detak Jantung Menggunakan Pulse Sensor Berbasis Raspberry - Putri Karina; Ahmad Hamim Thohari (Politeknik Negeri Batam, 2018)
Health is a prosperous state of body, soul, and social that enables everyone to live socially and economically productive. The heart is a vital organ in the body that affects health, heartbeat is one of the parameters that paramedics use to know health. Stethoscope is a common tool used in measuring heart rate, simple and easy to carry, but has a deficiency in its use directly by experts / medical who have knowledge of Stethoscope in achieving accurate results in accuracy requires concentration in finding results and Stethoscope itself can not be used by ordinary people who do not understand. Pulse and Raspberry sensor control using MCP3008 that serves as an analog to digital converter. Thus, it is hoped to detect the heart rate increase with ease accurately and the measurement can be done by itself. This final project proposes the design of heart rate measurers in a fast and accurate way in a relatively accurate calculation of results. The workings of this tool is to retrieve data from the pulse sensor detection for heartbeat and then displayed on the monitor screen.